Unexpected postpneumonectomy exertion-induced acute right heart failure. Issue 6 (December 2018) - Colombo, Jacopo; Arendar, Iryna; Pastorino, Ugo; Codazzi, Daniela
Introduction: Thoracic surgery can have serious side effects. Accurate preoperative evaluation to assess which patients with anatomically resectable disease are suitable candidates for surgery is mandatory. Case description: A 58-year-old man, scheduled for left pneumonectomy for lung cancer, passed all the preoperative examinations suggested by guidelines and underwent the surgery. Three days after pneumonectomy, he experienced hemorrhagic shock and subsequent acute respiratory distress syndrome. Fifteen days after left pneumonectomy, he experienced exertional acute right heart failure (ARHF). We administered sildenafil and he improved, clinically and echocardiographically. During the following 2 years of follow-up, he was asymptomatic at rest but under exercise test, he developed pulmonary hypertension with echocardiographic signs of right ventricular impairment. Conclusions: In patients scheduled for major lung resections, preoperative stress echocardiography may give an adjunctive value to cardiopulmonary exercise test, quantifying the exercise-induced reduction in right ventricle ejection fraction and identifying asymptomatic patients at risk for postoperative ARHF.